GEGAR BUDAYA PERANTAU DALAM SASTRA LISAN MINANGKABAU MALIN KUNDANG - Mina Elfira (Jurnal Pustaka Komunikasi, 2020)
The aim of this paper is to investigate how migration (marantau) culture is constructed in oral literature of Minangkabau, the worlds largest matrilineal society. A well known Malin Kundang oral literature is used as a source of analysis. By using literature sociological approach, and descriptive-criticism method, analysis of the texts, produced by Minangkabau matrifocal society, shows the weak relationship between a mother and her son. Moreover, it is used as educative media for Minangkabau people, who have implemented migration concepts as a part of the implementations of their matrilineal Adat (customary laws).The text also contains advices for Minangkabau migrants to never forget the Adat and native land despite the fact that their have migrated and adapted to rantau culture. The punishment for Malin Kundang, the main character of this oral literature, which has been cursed into stone by his own mother, can be taken as a representation of motherlands punishment for the migrants who have faced cultural shock, and forgotten the main purpose of their migration mission. It is expected by the Adat that Minangkabau men do marantau activities just for temporarily in order to gain prosperity and wisdom before going back to participate in developing their the homeland.